Dual IRE1 RNase functions dictate glioblastoma development. Issue 2 (8th February 2023) - Lhomond, Stéphanie; Avril, Tony; Dejeans, Nicolas; Voutetakis, Konstantinos; Doultsinos, Dimitrios; McMahon, Mari; Pineau, Raphaël; Obacz, Joanna; Papadodima, Olga; Jouan, Florence; Bourien, Heloise; Logotheti, Marianthi; et al.
Abstract :